MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE JIGSAW DALAM PEMBELAJARAN - Ahmad Syarifuddin (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2011)
Abstract In formal educational institutions such as schools, educational success can be seen from the results of student’s learning in academic achievement. The quality and success of student’s learning is strongly influenced by the ability and accuracy of teachers in choosing and using teaching methods. If Traditional learning model is compared to a more modern model this will results in less student’s involvement in learning activities. Students’ Activities were only just sitting, being silent, listening, recording and memorizing. It was also found out that the students were not participated in learning activities which made them quickly get bored and lazy . Under these conditions, It is needed to have learning-oriented alternative to the students so that students can learn on their own to find out information, connect the topics they have learned in everyday life, and can interact with both teachers and their peers in a fun and friendly atmosphere. One of the alternatives that can be used as educational experts have suggested is jigsaw cooperative learning type, which means the exchange of teams of experts. Kata Kunci: Models of learning cooperative learning, jigsaw